(untitled) (Journal Of Educational and Psychological Researches, 2015)
This study aims to recognize the process of using computer in publicschools in Ma`an governorate in terms of hardware, capabilities, and teachers usage. It also aims to identify the most important obstacles those schools face from a teachers perspective. The study sample consists of (150) teachers from different disciplines. The researcher prepared two questionnaires related to the research pivotal, then presented to a group of arbitrators to be used in this final form. The data was analyzed statistically and the study concluded that there is a shortage in the computer services provided to teachers, and there is a weakness in their use, there are high trends in this technique. Te study shows that there is a need to train teachers on this technology, and provide all the supplies that facilitate the use of computers in teaching, and the researcher provides several recommendations that perhaps might contribute to solve the problems faced computers users in teaching.